Dedifferentiation: the return road to repair the intestinal epithelium - Liu, Yuan (Cell Regen, 2020)
In the March 5 issue of Cell Stem Cell, (Murata K et al. Cell Stem Cell. 26(377–390):e376 2020) reported that intestinal stem cell recovery after injury is principally through Ascl2-dependent dedifferentiation of absorptive and secretory precursors in mice. This study provides evidence for robust regenerative capability of the intestinal epithelium via dedifferentiation of absorptive and secretory progenitors in the crypt.